Formation of New Macrocyclic Complexes with Bis (Dithiocarbamate) Ligand;Preparation, Structural Characterisation and Bacterial Activity - Hasan, Hasan A.; Yousif, Enaam I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The synthesis and characterisation of new macrocyclic binuclear metal(II) complexes derived from dithiocarbamate (DTC) ligand are reported. The reaction of a bis-secondary amine, CS2 and KOH resulted in the formation of the free ligand. Two approaches were implemented to synthesis the macrocyclic bis(dithiocarbamate) complexes; (i) from the reaction of the free ligand with a metal ion, and (ii) via a one-pot reaction. In the free ligand approach, complexes were obtained by the reaction of dithiocarbamate salt with the metal ions; CoII, ZnII and CdII. However, the one-pot reaction is based on the mixing of the bissecondary amine, CS2, KOH and metal(II) chloride. Physico-chemical analyses were implemented to characterise the ligand and its complexes. These include; elemental analysis, thermal analysis, FTIR, UV-Vis, mass spectroscopy, magnetic susceptibility, conductance, melting points and 1H, 13C- NMR spectroscopy. These studies indicated the formation of binuclear macrocyclic complexes of the general formula [M(L)]2 (M= CoII, ZnII and CdII), in which thier geometries about metal centers are tetrahedral. Antibacterial activity of the metal complexes indicated that they have more activity against investigated bacterial strains, compared to the free ligand.